Eigendom Verponding As Basis Owing Land Rigts By Legal Analysis Contrasting Judges Of Cassation And Judicial Review In Deciding The Dago Elos Land Dispute In Bandung (Case Study Kasasi Number. 934 K/Pdt/2019 Dan Putusan Peninjauan Kembali No.109 Pk/Pdt/20 - Nanang Aditia Permana (Fakultas Hukum Universitas Jenderal Soedirman, 2025)
The definition of agrarian is seen from the definition in the Basic Agrarian Law (UUPA), which can be seen in Article 1 paragraph (2), namely the definition of agrarian includes the earth, water and space and the natural resources contained therein. Land is one part of agrarian land, namely the surface of the earth or the face of the earth. In the Big Indonesian Dictionary, land is the surface of the earth or the layer of earth above it. The purpose of this study is to determine the ownership status of the former western eigendom verponding after being declared as land directly controlled by the state and to analyze the legal considerations of the cassation and judicial review judges who contradicted in deciding the Dago Elos land dispute in Bandung. Based on this research, it is found that the ownership status of former western eigendom verponding land after being declared as land directly controlled by the state will be given to a person or legal entity based on Priority Recipient Rights based on Presidential Decree. No. 32 of 1979. Where physical control is the main key to the registration of former western land rights that have become state land. However, the granting of state land former western rights can only be given if there is an agreement with the former right holder on the issue of compensation. If there is no agreement with the former eigendom right holder, the land administration cannot register its rights.